Susceptibility of bacterial isolates from community-acquired infections in sub-Saharan Africa and Asia to macrolide antibiotics - Lubell, Y; Turner, P; Ashley, E; White, N (2011)
Objective To review the literature on the susceptibility of common community pathogens in sub-Saharan Africa and Asia to the macrolide antibiotics. Methods Inclusion criteria required that isolates were collected since 2004 to ensure results were of contemporary relevance. The data were aggregated by region, age group and sterility of site of culture sample. Results A total of 51 studies were identified, which reported the macrolide antimicrobial susceptibilities of common bacterial pathogens isolated since 2004. In general, there was less macrolide resistance in African than in Asian isolates. Most African studies reported high levels of macrolide susceptibility in Streptococcus pneumoniae, whereas most Chinese studies reported high levels of resistance. There was very little information available for Gram-negative organisms. Conclusions Susceptibility of the pneumococcus to macrolides in SSA remains high in many areas, and good activity of azithromycin has been shown against Salmonellae spp. in Asia. In urban areas where high antibiotic consumption is prevalent, there was evidence of increased resistance to macrolides. However, there is no information on susceptibility from large areas in both continents. © 2011 Blackwell Publishing Ltd.